2014
DOI: 10.1177/1063426613520456
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Sustainability of an Evidence-Based Program

Abstract: Although numerous studies address the efficacy of school-based interventions, fewer focus on how to support sustainability of interventions from the perspective of participants. To address this research gap, we use the Practical, Robust Implementation and Sustainability Model to examine how the characteristics of an evidence-based program interact with those of participants (i.e., students, parents, educators) to influence program implementation and continuation. Specifically, we consider lessons learned in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…The satisfaction survey was collected by teachers and parents at postintervention, and assessed the perception of training and support received, program usability, and program effectiveness, with alphas of .91 and .94, respectively. Further details on all of the above measures are available in Sumi et al (2013), Walker et al (2009), and Woodbridge et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The satisfaction survey was collected by teachers and parents at postintervention, and assessed the perception of training and support received, program usability, and program effectiveness, with alphas of .91 and .94, respectively. Further details on all of the above measures are available in Sumi et al (2013), Walker et al (2009), and Woodbridge et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…There is a need to ensure that the strategies teachers use to address students' involvement in peer victimization and associated problem behaviors build from evidence-based research (Reinke & Herman, 2002;Rose & Monda-Amaya, 2012). There is a related need to establish service delivery structures that provide teachers with resources, supports, and guidance necessary to address the management of classroom behavior and social dynamics that contribute to the peer victimization process (Farmer et al, 2014;Motoca et al, 2014;Woodbridge et al, 2014).…”
Section: Implications For Service Deliverymentioning
confidence: 99%
“…School counselors, special educators, school psychologists, and other intervention support specialists may play a pivotal role in the reduction of peer victimization. These specialists can monitor individual students' social and emotional adaptation as well as the bullying climate at both the classroom and school levels, and they can provide direct services to students as well as act as a consultative resource to teachers (Lund et al, 2012;Motoca et al, 2014;Poduska & Kurki, 2014;Reinke et al, 2014;Woodbridge et al, 2014). As the field struggles with issues in the implementation and sustainability of evidencebased practices, it is necessary to understand that teachers cannot address students' peer victimization alone, and they need a range of services and supports to help them address the social needs of youth with disabilities who are vulnerable for involvement in the bullying process.…”
Section: Toward a National Program Of Research On Disability And Peer Victimizationmentioning
confidence: 99%
“…However, a previous study suggested that a positive school climate was associated with the continued implementation of school-based health intervention [ 53 ]. In addition, inadequate staffing and administrative support hindered the sustainment of school-based programs [ 54 , 55 ] .…”
Section: Discussionmentioning
confidence: 99%